Shift work is significantly and positively associated with possible gastro-esophageal reflux disease: A meta-analysis study - Chen, Hsiang-Tai; Chuang, Hung-Yi; Hsieh, Tsung-Yu; Wu, Pei-Shan; Lin, Fang-Jiun; Huang, Huan-Chih; Yang, Chen-Cheng; Kuo, Chao-Hung (Frontiers in Public Health, 2022)
Background One of the health issues related to shift work pattern is possible gastro-esophageal reflux disease (GERD) symptoms. However, the association between shift work and possible GERD symptoms through meta-analysis has not been developed in the current literature field. Therefore, the purpose of this study is to analyze the association between shift work and possible GERD symptoms through meta-analysis. Methods Studies containing target keywords were found in three datasets, and four articles were selected for further analysis after examining the title, abstract, and text. All prevalence odds ratios (ORs) among different groups of population and the standard error (SE) from each included study were calculated for conducting meta-analysis. Result The pooled OR has shown a significant positive association between shift work and possible GERD (OR 1.53; 95% confidence interval [CI] 1.33 - 1.77, p-value 0.003). Compared to non-shift workers, the subgroup analysis indicates there are positive associations between possible GERD and the night shift (OR 1.39; 95% CI 1.16 - 1.66), and the rotating shift (OR 1.83; 95% CI 1.44 - 2.33). The subgroup analysis has also shown similar trends in males shift workers (OR 1.28; 95% CI 1.03 - 1.60) and both genders shift workers (OR 1.75; 95% CI 1.45 - 2.11). Conclusion This study has shown a positive association between shift work and possible GERD.